Quantitative sustainability assessment of agricultural system in Singapore - Hu, Xiaoying (2018)
Singapore has limited land resources, and more than 90% of food consumed in local is imported. Sustainable development in agriculture is one of the most important national goals. Quantitative sustainability assessment provides a quantitative assessment of key performance indicators suitable for sustainability analysis and thus comparison of alternative processes as per their effect on sustainability metrics. Life cycle assessment (LCA) methodology is the standardized tool to quantitatively assess sustainability and is used in this project to validate the sustainable development of aquaculture systems. Two agricultural systems (soil vs hydroponic agriculture) are compared on the impacts on human health, productivity and global warming potential. By using LCA method and Openlca software, hydroponic cultivation method results in 0.7614 environmental impacts points, while 0.7691 points for soil cultivation method. The quantitative sustainability of soil cultivation system is strongly related to its poultry manure inputs, which has seriously affecting human health impacts. Hydroponic cultivation system depends more on the consumption electricity, resulting in impacts of global warming potential (0.5289 kg CO2e), 17.1% more than soil cultivation system. This project aims to help Singaporean agriculture farming to become a smart agriculture that is not only safer, but also more sustainable and highly efficient.